Metastatic Renal Cell Carcinoma to the Testis: A Clinicopathologic Analysis of Five Cases. (4th March 2020) - Wang, Gang; Zhou, Chen; Villamil, Carlos F.; So, Alan; Yuan, Ren; English, John C.; Jones, Edward C.
Abstract : The testicular spread of renal cell carcinoma is extremely rare. Five cases of renal cell carcinoma metastatic to the testis are described. The patients ranged from 45 to 81 years of age. Four of the five patients had known renal cell carcinoma. The time intervals between the partial and radical nephrectomies for the primary kidney tumors and the occurrence of testicular metastases ranged from 29 to 34 months. In one patient, the testicular mass was the initial presentation leading to a diagnosis of renal cell carcinoma. There were three ipsilateral metastases, one contralateral metastasis, and one bilateral metastasis. The metastatic deposits ranged in size from 2.0 to 5.7 cm. One case had multiple metastatic tumor nodules. All of the metastatic tumors had clear cell histological features, microscopically concordant with the primary renal cell carcinoma subtype. Three patients died of the disease 17 to 42 months after orchiectomy. One patient is alive with additional metastatic lesions 13 months after orchiectomy. One patient had been free of disease at 87 months after orchiectomy but is now on targeted therapy for an additional metastasis at 93 months after orchiectomy. To date, this report is one of the largest single series of patients with renal cell carcinoma metastatic to the testis, and it has the longest follow-up and survival among all the reported cases.